Effect of Preoperative Education on Patient Anxiety Level: A Scoping Review - Ensherah Althobiti; Ashwag Almashi; Ahlam Albawinei; Fatima Alnashri; Fatima Alsubaiea; Elham Al Nagshabandi; Maram Banakhar (Evidence-Based Nursing Research)
Context: A surgical intervention generally causes physical and psychological strain, which leads to excessive anxiety. The provision of knowledge and patient education during the preoperative period helps to reduce anxiety levels among surgical patients.